German ’zum’-PPs as adjective intensifiers - Lukassek, Julia; Ermakova, Maria; Nau, Juliane (Proceedings of Sinn und Bedeutung, 2022)
In this paper, we discuss a type of intensifiers that consists of a combination of the preposition zum with nominalised infinitives. We present an exploratory corpus study indicating that besides a small amount of highly lexicalised combinations, all components of the construction exhibit a high degree of flexibility in the material inserted. Based on this observation we argue that this is a productive pattern with some fully idiomatic representatives and propose a compositionally derived meaning constitution. The core meaning components are (i) a comparison of two adjectival properties conceptualised in terms of tropes, (ii) an attitudinal evaluative component and (iii) a modal operator accounting for non-referentiality effects of the internal PP-argument.